1999
DOI: 10.1056/nejm199906243402502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Systemic Glucocorticoids on Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Treatment with systemic glucocorticoids results in moderate improvement in clinical outcomes among patients hospitalized for exacerbations of COPD. The maximal benefit is obtained during the first two weeks of therapy. Hyperglycemia of sufficient severity to warrant treatment is the most frequent complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
424
2
49

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 766 publications
(497 citation statements)
references
References 19 publications
12
424
2
49
Order By: Relevance
“…Systemic glucocorticoids are frequently prescribed for exacerbations of the disease and have been shown to be effective in improving FEV1 [5], but even when given for exacerbations, the beneficial effects of systemic steroids appear to be limited to the first two weeks only [6].…”
mentioning
confidence: 99%
“…Systemic glucocorticoids are frequently prescribed for exacerbations of the disease and have been shown to be effective in improving FEV1 [5], but even when given for exacerbations, the beneficial effects of systemic steroids appear to be limited to the first two weeks only [6].…”
mentioning
confidence: 99%
“…Furthermore, corticosteroids can counteract bronchospasms, which can play a significant role in some cases of pneumonia (e.g. in patients with chronic obstructive pulmonary disease ⁄ asthma or virus-induced pneumonia) [29,30]. These potential beneficial effects of corticosteroids have been investigated in several clinical trials in which corticosteroids have been used as adjunctive therapy in patients with sepsis and septic shock as well as in those with pneumonia [28,[31][32][33][34][35][36].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…A systematic review suggested that systemic steroids result in physiologic improvement over the first 72 hours and reduced the odds of a treatment failure over the subsequent 30 days, although the risk of adverse drug reaction was increased (101). The largest study evaluated 271 patients from 25 Veterans Affairs medical centers (102). Patients were randomized to placebo or one of two steroid treatment arms (Solumedrol 125 mg/d for 3 d followed by either a 15-d or 8-wk taper).…”
Section: Therapeutic Approaches Generalmentioning
confidence: 99%